Deconstructing Ethnography: Towards a Social Methodology for Ubiquitous Computing and Interactive Systems Design - Button, Graham; Crabtree, Andy; Rouncefield, Mark; Tolmie, Peter (Human–Computer Interaction Series, 2015)
This book aims to deconstruct ethnography to alert systems designers, and other stakeholders, to the issues presented by new approaches that move beyond the studies of 'work' and 'work practice' within the social sciences (in particular anthropology and sociology). The theoretical and methodological apparatus of the social sciences distort the social and cultural world as lived in and understood by ordinary members, whose common-sense understandings shape the actual milieu into which systems are placed and used.In Deconstructing Ethnography the authors show how 'new' calls are returning systems design to 'old' and problematic ways of understanding the social. They argue that systems design can be appropriately grounded in the social through the ordinary methods that members use to order their actions and interactions.This work is written for post-graduate students and researchers alike, as well as design practitioners who have an interest in bringing the social to bear on design in a systematic rather than a piecemeal way. This is not a 'how to' book, but instead elaborates the foundations upon which the social can be systematically built into the design of ubiquitous and interactive systems.